Study of recurring typhus in Peru - Del Prado, Eliodoro (1920)
The recurring typhus, whose synonyms are so numerous, it is a disease that endemic and epidemic exacerbations character, cruelly whips the vast territory of Peru, in many localities causing mass casualties. The greatest tribute is for the indigenous people of our mountains, which, as we know, is more accessible to contagion, given their inveterate habits of uncleanliness.